Artificial Intelligence for Food Production among Smallholder Farmers: Towards Achieving Sustainable Development Goals (SDGs) in Nigeria - Amuda, Yusuff Jelili; Alabdul rahman, Sarah (Journal of Ecohumanism, 2024)
Smallholder farmers have been contributing to agricultural productivity in the country. Artificial intelligence (AI) has been growing and it has been playing positive roles in various sectors of the economy. The primary objective of this study is to explore artificial intelligence for food production among smallholder farmers in Nigeria in order to achieve sustainable development goals (SDGs) in the country. Content analysis and systematic literature review is used in this study. The findings of the study demonstrated that the application of artificial intelligence can contribute to realization of SDG 2 (Zero Hunger) with appropriate government interventions in the sector. In addition, it is also shown that artificial intelligence (AI) can be used for weeding, spraying pesticides, monitoring livestock, and automating harvesting processes. It is further noted that digitalization of agriculture through AI tools reduces middlemen, expands market opportunities, and enhances productivity and livelihoods of small-scale farmers. It is therefore suggested that the stakeholders in the agricultural sector should actively involve in training smallholder farmers in digital skills for efficient application of AI.